Microbiome Modulation After Bariatric Surgery: A Potential Link to Diverticulitis - Mahmood, Ali; Yaakovian, Michael; Ali, Aman Barkat; Desai, Svetang Vijay; Mahmood, Aiva Mariam; Mahmood, Emaan Anya (British Journal of Healthcare and Medical Research, 2025)
Background: Diverticulitis is an increasingly prevalent gastrointestinal condition in the United States, with rising incidence, recurrent disease burden, and significant morbidity. Obesity is a well-established risk factor for both the development and complications of diverticulitis, and emerging evidence highlights the gastrointestinal microbiome as a key mediator of intestinal inflammation. Bariatric surgery induces profound alterations in gastrointestinal anatomy, physiology, and microbial composition. However, the relationship between post-bariatric microbiome changes and diverticular disease remains poorly understood. Objective: To evaluate the impact of bariatric surgery—particularly the microbial and physiologic changes following gastric bypass—on the development, recurrence, and severity of diverticulitis. Methods: We conducted a retrospective review of all patients undergoing bariatric surgery between January 1, 2024, and January 1, 2025. Patient records were examined for prior history of diverticulitis, postoperative incidence of diverticulitis, disease severity, and need for medical or surgical intervention. Microbiome-related data were contextualized using current literature on microbial patterns associated with obesity, post-bariatric physiology, and diverticular inflammation. Results: Bariatric surgery is known to induce substantial shifts in gut microbial ecology, including increased microbial diversity, changes in bile-acid–metabolizing species, and reduced abundance of pro-inflammatory taxa. These shifts may theoretically mitigate obesity-associated inflammatory risk, yet they may also influence mucosal vulnerability within existing diverticula. Over the study period, the bariatric surgery and colorectal surgery services jointly managed 16 mutual patients. Among these, 4 patients required sigmoid resection for diverticulitis. Compared to the prior calendar year—during which only 1 mutual patient underwent sigmoid resection—this represents a four-fold increase. Conclusions: The interplay between bariatric surgery, the gastrointestinal microbiome, and diverticulitis is multifactorial and incompletely defined. While weight loss and improved metabolic health may reduce overall inflammatory risk, surgery-induced microbial shifts could modulate susceptibility to diverticular inflammation in unpredictable ways. Further prospective, microbiome-focused studies are needed to clarify these mechanisms and inform personalized risk stratification and postoperative management for bariatric patients with known or potential diverticular disease.